Fritz Schmidt (1882–1950) and his pioneering work of current value accounting in comparison to Edwards and Bell's theory* - MATTESSICH, RICHARD V. (Contemporary Accounting Research, 1986)
One of the tasks of this paper is to draw attention to Fritz Schmidt and his pioneering work in current value accounting which anticipated essential features of both Edwards and Bell's (1961) work by 40 years, and the current cost legislations and standards of the United Kingdom, the United States, and Canada by roughly six decades. Above all, I am trying to relate Schmidt's work to that of Edwards and Bell, thereby clarifying some misunderstandings that still surround this relationship. Schmidt needs a champion on the North American continent, and I have tried to assume this often misunderstood task. By direct reference to and translations from Schmidt's magnum opus , I attempt to demonstrate that Schmidt's theory possesses the following qualities: It distinguishes clearly between general purchasing power adjustments and current value adjustments. It does eliminate realized holding gains (cost savings) from the operating section, and presents an income concept equivalent to the “Current Operating Profit” of Edwards and Bell. It clearly separates operating gains from holding gains (though rarely endeavors to separate real from fictional holding gains, since it favors the physical capital maintenance basis of income measurement). It applies current costs also to manufacturing operations. It does not fail to deal with the current costs of other inputs, and generally abandons the historical cost basis. Résumé. Un des objectifs de cet article, est de faire ressortir le travail de pionier de Fritz Schmidt sur la comptabilité à la valeur actuelle qui anticipa les caractéristiques essentielles des travaux de Edwards et Bell (1961) de 40 ans et les lois et normes sur le coût actuel du Royaume‐Uni, des Etats‐Unis et du Canada d'approximativement six décades. Avant tout, j'essaie de relier les travaux de Schmidt à ceux de Edwards et Bell, afin de clarifier certaines méprises qui existent toujours relatives à cette relation. Schmidt a besoin d'un champion sur le continent nord américain et j'ai essayé d'assumer cette tâche souvent mal comprise. En me référant aux travaux de Schmidt et à certaines traductions, j'essaie de démontrer que la théorie de Schmidt possède les qualités suivantes: Elle distingue clairement les ajustements du pouvoir général d'achat des ajustements de la valeur actuelle. Elle élimine les gains de détention réalisés (économies de coûts) de la section exploitation et présente un concept de revenu équivalent au “Bénéfice hors postes non courants” de Edwards et Bell. Elle sépare clairement les gains d'exploitation des gains de détention (quoiqu'elle ne s'efforce pas de séparer les gains de détention réels des fictifs, puisqu'elle favorise la base de la préservation de la capacité de production pour mesurer le revenu). Elle utilise les coûts actuels aussi pour les exploitations manufacturières. Elle n'oublie pas de traiter des coûts actuels des autres intrants et abandonne de façon générale la base du coût historique.